EVALUATION OF POST ABORTION AND POSTPARTUM PATIENTS IN ULTRASOUND (The Research of Medical Science Review, 2025)
Introduction: This study assesses post-abortion and postpartum patients through ultrasound in order to recognize complications and enhance maternal health outcomes. It underscores the necessity of understanding female reproductive anatomy and employing ultrasound—specifically transvaginal and pelvic methods—to identify issues such as retained products of conception (RPOC), uterine rupture, endometritis, and vascular abnormalities. The research highlights the utility of ultrasound as a non-invasive and cost-effective diagnostic approach for complications like postpartum hemorrhage, pelvic injuries, and infections that arise in the postpartum and post-abortion phases. Material and Method: A cross-sectional study conducted at Mian Trust Hospital in Faisalabad involved 70 women aged 18-50 who were examined using high-frequency ultrasound probes. The results indicated a significant occurrence of RPOC, myometrial hyper vascularity, and uterine alterations following both C-section and vaginal deliveries. This study emphasizes the vital importance of ultrasound in the early detection and management of complications, recommending routine evaluations postpartum and post-abortion to improve maternal health outcomes.Result: The descriptive statistics indicate that among 70 cases, clinical and ultrasound findings showed varying mean values, with the highest mean for cervical trauma (1.5286) and the lowest for gestational sac (1.0571). Standard deviations were relatively low across findings, indicating minimal variation within the dataset. Discussion: Ultrasound imaging plays a vital role in obstetrics particularly in the post-abortion and post- partum patients. This non-invasive and cost- effective tool provides critical insighights into pelvic anatomy, identifying complications. The ability of ultrasound to offer immediate diagnostic capabilities make it indispensable in maternal case. This document also underscores the importance of using Trans abdominal and Transvaginal ultrasound to evaluate the conditions comprehensively. Conclusion: This study emphasizes the vital role of ultrasound in diagnosing post- abortion and postpartum complications, such as retained products of conception (RPOC), endometritis, and uterine abnormalities. RPOC was the most common issue (50%), often linked to vaginal bleeding, while endometritis was associated with anechoic fluid or RPOC. The findings highlight the importance of age-specific diagnostic and management strategies to improve maternal health outcomes.